2013
DOI: 10.1136/bjophthalmol-2012-302726
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the rate of esotropia surgery in the United Kingdom from 2000 to 2010

Abstract: Rates of strabismus surgery in children, especially for esotropia, continued to decrease between 2000 and 2006, but may have stabilised from 2006 to 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The reduction in the amount of strabismus surgery performed on children over the 14‐year period examined is consistent with previous studies, which also found a decline in paediatric surgery in earlier time periods in England, Scotland, and Canada (although this doesn't appear to be the case in the United States). Paediatric strabismus surgery appears to have been declining from at least as early as 1968: strabismus operations on children decreased from 189 to 64 episodes per 100,000 population between 1968 and 2010 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The reduction in the amount of strabismus surgery performed on children over the 14‐year period examined is consistent with previous studies, which also found a decline in paediatric surgery in earlier time periods in England, Scotland, and Canada (although this doesn't appear to be the case in the United States). Paediatric strabismus surgery appears to have been declining from at least as early as 1968: strabismus operations on children decreased from 189 to 64 episodes per 100,000 population between 1968 and 2010 …”
Section: Discussionsupporting
confidence: 89%
“…This issue is relevant to studies that have investigated changes in the frequency of paediatric strabismus surgery because they don't include figures for all children. 9,10,12 It also means that it's theoretically possible that the increases we observe for strabismus surgery on patients aged 15 years or older could be driven by changes in surgery rates for children aged 15 years. However, we are confident this is not the case for the following reasons.…”
Section: Operations For Horizontal Deviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data based on the clinical reviews in Hong Kong and Singapore supported the same trend [ 4 , 5 ]. It is also implied from studies that surgery for childhood esotropia was much more common than surgery for exotropia, although the proportion of surgery for esotropia has continued to decline in UK [ 6 8 ], Italy [ 9 ], and USA [ 10 ]. While a study based on an eye center of China showed that surgery for concomitant exotropia was more common than those for esotropia, the amounts of surgery for esotropia also increased from 2003 to 2006.…”
Section: Introductionmentioning
confidence: 99%